Optimization of no cook technology at very high gravity for rice-based ethanol production - Thi Phuong, Vu; Nguyen, Chinh Nghia; Vu Hong, Son; Chu, Ky Son (Vietnam Journal of Science and Technology, 2023)
The application of raw-starch hydrolysis enzymes to ethanol production by no-cook technology at very high gravity (VHG) (311.5 g/L) from rice would reduce the energy consumption compared to traditional process. In this study, the Taguchi design and the desirability function were used to identify the optimized production process for economic and technological targets. Three factors: dosage of alpha- and gluco-amylase enzyme (Stargen 002 – A), dosage of protease enzyme (Fermgen – B) and dosage of yeast (C) were investigated. With the expected Desirability = 0.74, the no-cook process from rice would be optimized with following dosage: Stargen 002, Fermgen and yeast at 700 µL/L (1140 GAU/kg raw material), 151 µL/L (431 SAPU/kg raw material) and 0.25 g/L (6.25 x 106 cells/mL), respectively. After 120h of fermentation, ethanol concentration reached 17.45 ± 0.07 %v/v, corresponding to ethanol yield of 86.08 ± 0.2 %, and the cost of raw material was at 3225.5 VND/L of rice slurry.